The Impact of Non-caloric Sweeteners on Male Fertility: A Systematic Review and Narrative Synthesis in Rodent Models - Kearns, Michelle L.; MacAindriu, Fionn; Reynolds, Clare M. (Frontiers in Nutrition, 2022)
Understanding the factors which influence fertility is essential for developing appropriate nutritional recommendations for couples trying to conceive. Non-caloric sweeteners (NCS) are increasing in the food chain and despite being no/low calorie, several adverse metabolic consequences have been attributed to their consumption. Their effects on reproduction have been relatively under-researched, particularly in males. This review aims to systematically review the literature for evidence of the effect of NCS on male fertility in rodents, with sperm parameters (sperm quantity and quality) assessed as primary outcomes. Given the lack of information available in humans this review has been carried out using evidence from rodent models. Risk of bias assessment was carried out using the Syrcle risk of bias tool. Nine studies met the inclusion criteria. Forty-four percent showed a negative effect of NCS on male reproductive parameters compared with controls. The effects of NCS on fertility have been conflicting and selected studies have been heterogeneous in relation to study design. It is unclear if NCS has an impact on male reproductive function. There is a need for randomized controlled trials using a standardized protocol for analysis, to formulate a clear message in terms of male fertility.